CFD simulation-based predesign of an advanced gas-diesel combustion concept. (December 2021) - Winter, Hubert; Aßmus, Kevin; Redtenbacher, Christoph; Dimitrov, Dimitar; Wimmer, Andreas
The greenhouse gas saving potential of using gaseous fuels with high methane content (e.g. natural gas) in internal combustion engines instead of conventional liquid fossil fuels (e.g. petrol, diesel) is considerable due to the comparatively low emission of carbon dioxide resulting from the low C/H ratio of methane. However, to fully exploit this potential, it is of utmost importance to keep methane slip at a very low level. In contrast to mixture aspirated gas engines and diesel-gas engines, the gas-diesel combustion concept avoids methane slip nearly completely since the gaseous fuel is directly injected into the combustion chamber at the end of the high-pressure phase of the engine cycle, resulting in mixing-controlled combustion with low emission of unburned hydrocarbons. An advanced high-speed large engine concept based on the gas-diesel combustion process was developed. An effective and reliable virtual design methodology was applied during the development of the concept. The methodology comprehensively combines 3D CFD and 1D simulation tools in the combustion concept predesign phase with experiments on a single-cylinder research engine in the concept validation phase. A major challenge in the virtual design of this dual fuel combustion process is the large number of degrees of freedom that result in particular from the use of a fully flexible combined gas/diesel injector. This paper describes in detail the role of 3D CFD simulation in this approach, which allows precise prediction of the optimal geometries and operating strategies for high-efficiency and low-emission engine operation.